2014
DOI: 10.4038/kjhrm.v9i1-2.15
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Work Life Balance and Employee Performance: With Reference to Telecommunication Industry of Sri Lanka

Abstract: In today's dynamic business environment, work life balance has become one ofthe key issues faced by many employees all over the world. Maintaining work life balance is an issue increasingly recognized as ofstrategic importance to organization and of significance to employees. A lack of work life balance also has an adverse effect on their employer's prospects for success in many respects. The main objective ofthis study is to carry out research on the Sri Lankan telecommunication industry and recognize the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Knowledge management will help organizations absorb different opinions and experiences, thereby improving quality in the decision-making process. Knowledge management will make it easier to find information and find people who have the information needed by the organization (Darroch, 2005;Knorr-Siedow & Tosics, 2005;Mendis, M.D.V.S. and Weerakkody, 2014;Musa & Usman, 2012).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Knowledge management will help organizations absorb different opinions and experiences, thereby improving quality in the decision-making process. Knowledge management will make it easier to find information and find people who have the information needed by the organization (Darroch, 2005;Knorr-Siedow & Tosics, 2005;Mendis, M.D.V.S. and Weerakkody, 2014;Musa & Usman, 2012).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…This would eventually make them focus more on their job as their worries about their life had been casted aside resulting in lower presenteeism. This result was supported by empirical studies that have showed positive effect of work-life balance on employees' performance and organizational performance (Hussein et al, 2018;Johari et al, 2018;Mendis & Weerakkody, 2014) and on job satisfaction, commitment and productivity (Mukururi & Ngari, 2014). Nevertheless, poor work-life balance will negatively affect the employees' perceived job stress, hence reducing the productivity of the employees (Bell et al, 2012).…”
Section: Factors Affecting Presenteeism Of Employeesmentioning
confidence: 66%
“…A significant number of empirical studies have showed that work-life balance is positively related to employees' performance and organizational performance (Harrington & Ladge, 2009;Mendis & Weerakkody, 2014;Rego & Pina e Cunha, 2009). Employees who successfully fulfill the role and commitment of families will demonstrate more excellent job performance.…”
Section: Work-life Balancementioning
confidence: 99%
See 1 more Smart Citation
“…Work-life balance involves the modification of work arrangements so as to allow workers to amalgamate work responsibilities and family tasks. Satisfying a healthy work-life balance is a matter which has increased recognition being strategic and important to the organisations since the hours at which an individual employee is scheduled to work and work-life balance affects their mental, health, physical and well-being (Mendis & Weerakkody, 2014). Work-life balance therefore comprises components such as flexible work arrangements which allow workers to execute other life programs and practices.…”
Section: Introductionmentioning
confidence: 99%